2010
DOI: 10.1002/nme.3053
|View full text |Cite
|
Sign up to set email alerts
|

Complementarity framework for non‐linear dynamic analysis of skeletal structures with softening plastic hinges

Abstract: SUMMARYIn this paper, we describe an algorithm for the incremental state update of elasto-plastic systems with softening. The algorithm uses a complementary pivoting technique and is based on casting the incremental state update as a complementarity problem. In developing the algorithm, we take advantage of the special features of solid and structural mechanics problems to achieve good computational performance, and hence the ability to compute numerical solutions to practical size problems. For example, the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…We refer to the Fenchel–Legendre transforms of these functions as the complementary stored energy function ψ c ( σ , ξ ) and the complementary dissipation function φ c ( σ , ξ ), where σ is the stress and ξ is the generalized stress conjugate to α . With linearized kinematics, it can be shown that incremental state update can be formulated as a convex minimization problem in ( σ , ξ ) , which we term the primal problem.…”
Section: Primal Problem Of Incremental State Updatementioning
confidence: 99%
See 4 more Smart Citations
“…We refer to the Fenchel–Legendre transforms of these functions as the complementary stored energy function ψ c ( σ , ξ ) and the complementary dissipation function φ c ( σ , ξ ), where σ is the stress and ξ is the generalized stress conjugate to α . With linearized kinematics, it can be shown that incremental state update can be formulated as a convex minimization problem in ( σ , ξ ) , which we term the primal problem.…”
Section: Primal Problem Of Incremental State Updatementioning
confidence: 99%
“…This mathematical programming approach was first introduced by Maier [25]. 904 Z. LOTFIAN AND M. V. SIVASELVAN Use of mathematical programming for state update has several attractive features [26]. Models of frictional contact, plasticity, damage and phase changes are often described using different formalisms of nonsmooth mechanics, including nonsmooth energy and dissipation potentials [27][28][29], variational inequalities [30,31] and hemi-variational inequalities [32,33].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations